Proteomics and lipidomic analysis reveal dysregulated pathways associated with loss of sacsin - Galatolo, Daniele; Rocchiccioli, Silvia; Di Giorgi, Nicoletta; Dal Canto, Flavio; Signore, Giovanni; Morani, Federica; Ceccherini, Elisa; Doccini, Stefano; Santorelli, Filippo Maria (Frontiers in Neuroscience, 2024)
Introduction Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a rare incurable neurodegenerative disease caused by mutations in the SACS gene, which codes for sacsin, a large protein involved in protein homeostasis, mitochondrial function, cytoskeletal dynamics, autophagy, cell adhesion and vesicle trafficking. However, the pathogenic mechanisms underlying sacsin dysfunction are still largely uncharacterized, and so attempts to develop therapies are still in the early stages. Methods To achieve further understanding of how processes are altered by loss of sacsin, we used untargeted proteomics to compare protein profiles in ARSACS fibroblasts versus controls. Results Our analyses confirmed the involvement of known biological pathways and also implicated calcium and lipid homeostasis in ARSACS skin fibroblasts, a finding further verified in SH-SY5Y SACS–/– cells. Validation through mass spectrometry-based analysis and comparative quantification of lipids by LC-MS in fibroblasts revealed increased levels of ceramides coupled with a reduction of diacylglycerols. Discussion In addition to confirming aberrant Ca2+ homeostasis in ARSACS, this study described abnormal lipid levels associated with loss of sacsin.